2020
DOI: 10.3390/foods9020119
|View full text |Cite
|
Sign up to set email alerts
|

Growth Behavior of Listeria monocytogenes in a Traditional Norwegian Fermented Fish Product (Rakfisk), and Its Inhibition through Bacteriophage Addition

Abstract: Listeria monocytogenes may persist in food production environments and cause listeriosis. In Norway, a product of concern is the traditional and popular fermented fish product “rakfisk”, which is made from freshwater salmonid fish by mild-salting and brine maturation at low temperatures for several months. It is eaten without any heat treatment, and L. monocytogenes, therefore, poses a potential hazard. We investigated the effect of salt and temperature on the growth of L. monocytogenes in rakfisk during the 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 35 publications
1
13
1
Order By: Relevance
“…More in general, our findings are in accordance with Rong et al (2014) [ 27 ] who demonstrated that the use of lower MOIs to reduce the presence of Vibrio parahaemolyticus during the depuration of oysters resulted as the best choice. In contrast with this study, others showed that higher MOIs (>1) led to a higher reduction of pathogen loads, also depending on the type of food, with greater reduction of Listeria in liquid food compared to the solid ones [ 5 , 6 , 18 , 28 , 29 ]. Ayaz et al (2018) [ 30 ] instead, showed that the application of different MOIs did not lead to significant differences in the bacterial counts.…”
Section: Resultscontrasting
confidence: 99%
“…More in general, our findings are in accordance with Rong et al (2014) [ 27 ] who demonstrated that the use of lower MOIs to reduce the presence of Vibrio parahaemolyticus during the depuration of oysters resulted as the best choice. In contrast with this study, others showed that higher MOIs (>1) led to a higher reduction of pathogen loads, also depending on the type of food, with greater reduction of Listeria in liquid food compared to the solid ones [ 5 , 6 , 18 , 28 , 29 ]. Ayaz et al (2018) [ 30 ] instead, showed that the application of different MOIs did not lead to significant differences in the bacterial counts.…”
Section: Resultscontrasting
confidence: 99%
“…Results provided by many authors are consistent that in general, increasing the initial phage/ Listeria ratio (either by reducing L. monocytogenes titration or by increasing phage titration) enhanced the efficacy of the phage in reducing bacterial populations [ 28 , 39 , 44 , 49 , 50 , 52 , 60 , 70 ]. Apart from tested food models, under real conditions in food products using a sufficiently high titer of phage suspension at the beginning of the treatment, without relying on self-amplification is crucial.…”
Section: Listeria Monocytogenes Bacteriophagessupporting
confidence: 56%
“…In addition to sensory analysis, numerous microbiological measurements, such as total viable count (TVC), have been widely applied and considered as standard tools used in order to validate the shelf life and demonstrate changes in the quality of meat and fish or other products. Microbial growth and microbiological analysis are especially important in the case of fermented products, such as fermented fish and seafood [11,25,[50][51][52]. Various types of microorganisms and different counts have been reported in the literature according to traditional processing processes (i.e., fermentation, drying, smoking, etc.)…”
Section: Classical Methods Used To Evaluate Quality Changesmentioning
confidence: 99%